Indirect photodegradation of ofloxacin in simulated seawater: Important roles of DOM and environmental factors - Liu, Shukai; Cui, Zhengguo; Bai, Ying; Ding, Dongsheng; Yin, Junshuang; Su, Rongguo; Qu, Keming (Frontiers in Marine Science, 2023)
Dissolved organic matter (DOM) plays a non-negligible role in the indirect photodegradation of organic contaminants. This research investigated the roles of DOM and the environmental factors (salinity, pH, NO3−, and HCO3−) in the indirect photodegradation of ofloxacin (OFX) in simulated seawater. Results showed that DOM can significantly accelerate the indirect photodegradation of OFX, and 1O2 and 3DOM* were the main reactive intermediates (RIs) that could promote the indirect photodegradation of OFX. Fluorescence excitation–emission matrix spectroscopy–parallel factor analysis (EEMs-PARAFAC) was used to divide DOM into four fluorescence components. The indirect photodegradation rate of OFX was affected by DOM structure, and terrigenous DOM usually produced more RIs to promote the indirect photodegradation of OFX. Increased salinity significantly promotes the indirect photodegradation of OFX, while increased NO3− concentration had no effect on the OFX indirect photodegradation. pH affected the formation of RIs and the structure of OFX, thereby affecting the indirect photodegradation of OFX. The indirect photodegradation rate of OFX increased in the HCO3− solution, which is due to the formation of carbonate radical (CO3−). This study is essential in understanding the role of DOM in OFX indirect photodegradation and providing a novel insight into the fate, removal, and transformation of OFX.